Coping and life satisfaction in colombian older adults (2021)
Background. Effective coping strategies facilitate older adults’ optimal adaptation and contribute to their well-being. Problem-focused strategies are associated with active styles and enhance well-being. This study analyzes the role of coping strategies in Colombian older adults’ subjective well-being (SWB) using structural equation modelling. Additionally, Confirmatory Factor Analyses of the Life Satisfaction Scale and Coping Strategies Questionnaires are performed. Method. A cross-sectional study is conducted with 455 Colombian older adults, ranging from 65 to 92 years old. Results. The results show that problem-focused coping has a positive effect on SWB, whereas emotion-focused coping has a negative effect on SWB. Conclusions. This article highlights the relationship between effective coping and life satisfaction by showing that problem-focused coping strategies are adaptative and enhance well-being during aging